2013
DOI: 10.1186/1471-2296-14-74
|View full text |Cite
|
Sign up to set email alerts
|

Survival of stroke patients after introduction of the ‘Dutch Transmural Protocol TIA/CVA’

Abstract: BackgroundEarlier research showed that healthcare in stroke could be better organized, aiming for improved survival and less comorbidity. Therefore, in 2004 the Dutch College of General Practitioners (NHG) and the Dutch Association of Neurology (NVN) introduced the ‘Dutch Transmural Protocol TIA/CVA’ (the LTA) to improve survival, minimize the risk of stroke recurrence, and increase quality of life after stroke. This study examines whether survival improved after implementation of the new protocol, and whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Although of different origin, the TIA effect on long-term mortality is similar in the general population and in patients submitted to carotid revascularization: as a matter of fact, the 78% 5-year survival of our study compares well with the 58% to 87% of the cohort studies in the general population. 22,23 Therefore, TIA can be considered an indicator of clinical impairment independent of its pathogenesis, as confirmed from our analysis in which, before surgery, symptomatic patients had similar long-term mortality rate regardless of the onset of other postoperative events.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Although of different origin, the TIA effect on long-term mortality is similar in the general population and in patients submitted to carotid revascularization: as a matter of fact, the 78% 5-year survival of our study compares well with the 58% to 87% of the cohort studies in the general population. 22,23 Therefore, TIA can be considered an indicator of clinical impairment independent of its pathogenesis, as confirmed from our analysis in which, before surgery, symptomatic patients had similar long-term mortality rate regardless of the onset of other postoperative events.…”
Section: Discussionsupporting
confidence: 68%
“…22 Similarly, the Dutch TIA Trial showed 60% mortality at 10 years in patients who had a TIA. 23 There is a variety of possible TIA causes in the general populationdsuch as cardiac rhythm alteration or great vessels atherosclerosisdthat can be a cause of late death; differently, TIAs after carotid revascularization are primarily associated with intraprocedural or periprocedural embolization. The majority of TIAs, in our study, occurred in the CAS group.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, lifestyle advice was offered to only one in four patients [ 14 ]. After the introduction of the Dutch protocol, only minimal impact was noted on clinical practice and no major changes in survival or secondary outcomes were found [ 15 ].…”
Section: Introductionmentioning
confidence: 99%